2007
DOI: 10.1353/hub.2007.0021
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and Genetic Correlations of Metabolic Disease-Related Phenotypes in Mexico: Preliminary Report from the GEMM Family Study

Abstract: Cardiovascular disease (CVD) is a major cause of mortality in the Republic of Mexico, and metabolic syndrome, a complex of CVD risk factors, is increasingly prevalent. To date, however, there have been few studies of the genetic epidemiology of metabolic syndrome in Mexico. As a first step in implementing the GEMM Family Study, a large, multicenter collaborative study, we recruited 375 individuals in 21 extended families, without ascertainment on disease, at 9 medical institutions across Mexico. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
15
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 22 publications
7
15
0
3
Order By: Relevance
“…This lack of correlation could be due to changes in the expression of genes during the growth process, affecting, therefore, covariation with BP phenotypes. However, our results are consistent with those observed in other adult populations such as the Mexican and Indians [7,14] in which no shared genetic effects were found between BP and these obesity traits. In summary, the reasons for the divergent results remain unclear and the absence of genetic correlations for some pairs of factors could be explained by the effect of age or by different genetic backgrounds among populations or by the sum of both.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This lack of correlation could be due to changes in the expression of genes during the growth process, affecting, therefore, covariation with BP phenotypes. However, our results are consistent with those observed in other adult populations such as the Mexican and Indians [7,14] in which no shared genetic effects were found between BP and these obesity traits. In summary, the reasons for the divergent results remain unclear and the absence of genetic correlations for some pairs of factors could be explained by the effect of age or by different genetic backgrounds among populations or by the sum of both.…”
Section: Discussionsupporting
confidence: 92%
“…The most commonly reported adiposity measures in relation to BP phenotypes include weight, waist circumference, skinfolds thickness and indices such as BMI and waist-to-hip ratio (WHR) [7][8][9][10][11][12][13][14]. Factors extracted from a factor analysis could represent features that contain a higher degree of genetic variance than the original variables separately [15].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the complex and unique structure of these Roma people pedigrees seems to provide valid and robust information about the genetic and environmental contribution to variation in obesity-related traits. Our data are in agreement with previous studies, where heritability of obesity-related phenotypes were estimated in Indians (Mathias et al 2009;Zabaneh et al 2009), Western Eurasians (Hasselbalch et al 2008;Poveda et al 2010;Jelenkovic et al 2011), Mexicans (Bastarrachea et al 2007) and Arabs (Bayoumi et al 2007). The results of this study are also comparable to those reported in other overweight populations such as Samoans (Choh et al 2001) and Mexican Americans (Comuzzie et al 1994).…”
Section: Discussionsupporting
confidence: 93%
“…Pleiotropy was also found for an elevated number of pairs. The phenotypic, genetic and environmental correlations estimated from the present study are mostly in line with previous studies (Choh et al 2001;Schousboe et al 2004;Bastarrachea et al 2007;Hasselbalch et al 2008;Mathias et al 2009). The high phenotypic, genetic and environmental correlation for BMI-SF reported in the present study, which is in agreement with the studies of Hasselbalch et al (2008) and Schousboe et al (2004), indicate that variation in body mass is highly associated with variation in adiposity.…”
Section: Discussionsupporting
confidence: 91%
“…(10) . Although we neither had an adequate sample nor a broad design of nuclear families to assess the genetic component (which decreases the study's statistical power), it seemed interesting to us to assess the h 2 of insulin resistance (IR) among parents with DMT2 and their descendants, in order to estimate the environmental contribution…”
Section: El Objetivo General Del Estudio Fue Explorar La Disposición mentioning
confidence: 99%